Design and implementation of control system for transport robot based on STM32 microcontroller - Mingliang, Zhang; Liquan, Guo; Chen, He; Benkun, Bao; Ziwei, Lu (2021 IEEE International Conference on Artificial Intelligence and Computer Applications (ICAICA), 2021)
A kind of electric and pneumatic joint control system for transport robot was proposed, and the system implementation was given. A transport robot and a 3D model built by SolidWorks were provided to illustrate the control system. The control system adopted the driving method of motor and cylinder, and took STM32 microcontroller as the control core. In order to improve the control precision and compliance of the system, the position loop and speed loop were used to establish the double closed loop PID control. In order to verify the performance of the system, 25 handling experiments were carried out for four kinds of box workpiece with mass of 1kg, 2kg, 3kg and 4kg respectively. The results show that the system can control the transport robot to complete the handling of the box workpiece. The system has a fast response and it is stable.